Local direct democracy in Europe - Schiller, Theo.; SpringerLink (Online service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
Modern direct democracy has recently become an important element of political life in many countries. These developments can be observed at the national, regional, and local level of political systems. Participation and democracy in local political affairs play a major role in stabilising and developing democratic systems. This volume presents, for the first time, a broad basis of information on the wide variety of local institutions and practice of direct democracy in 19 countries. Country specialists analyse: the role of direct democracy in the institutional; context and culture of national political systems; political processes of introduction and development of initiatives and referendums; regulations of procedures of municipal direct democracy; practice of local direct democracy; the contribution of local direct democracy to democratic development in general. - Publisher's description.
Local Direct Democracy in Europe A Comparative Overview - Emerging Patterns: Czech Republic - Germany - Italy - Norway - Poland - Switzerland - A Comparison of Eight Municipalities from Four Countries - Small Beginnings: Great Britain - Bulgaria - Denmark - Finland - France - Slovakia - Slovenia - Sweden - Estonia, Latvia, Lithuania; Articles by Theo Schiller, Michael L. Smith, PierVincenzo Uleri, Aimée Lind Adamiak, Andrzej K. Piasecki, Michael Buetzer, Wilfried Marxer, Zoltán Tibor Pállinger, Michèle Breuillard, Iva Taralezhkova, Palle Svensson, Rolf Büchi, Stéphane Guérard, Erik Lá'tic, Bernard Ne'mah, Bruno Kaufmann.
Electronic reproduction.
Keywords: Direct democracy -- Europe -- Congresses; Referendum -- Europe -- Congresses; Political participation -- Europe -- Congresses; Local government -- Europe -- Congresses; Europe -- Politics and government -- 1989- -- Congresses; Electronic books